Cyclotides - Michelle F. S. Pinto; Renato G. Almeida; William F. Porto; Isabel C. M. Fensterseifer; Loiane A. Lima; Simoni C. Dias PhD; Octávio L. Franco PhD (SAGE Publishing, 2012)
In recent years, a number of peptides containing a cyclic structural fold have been described. Among them, the cyclotides family was widely reported in different plant tissues, being composed of small cyclic peptides containing 6 conserved cysteine residues connected by disulfide bonds and forming a cysteine-binding cyclic structure known as a cyclic cysteine knot. This structural scaffold is responsible for an enhanced structural stability against chemical, thermal, and proteolytic degradation. Because of the observed stability and multifunctionality, including insecticidal, antimicrobial, and anti-HIV (human immunodeficiency virus) action, much effort has gone into trying to elucidate the structural-function relations of cyclotide compounds. This review focuses on the novelties involving gene structure, precursor formation and processing, and protein folding of the cyclotide family, shedding some light on molecular mechanisms of cyclotide production. Because cyclotides are clear targets for drug development and also biotechnology applications, their chemical synthesis, heterologous systems production, and protein grafting are also addressed.